Cartera de crédito vencida de la Cooperativa de Ahorro y Crédito Juan Pio de Mora Ltda. Ubicada en Caluma durante el periodo 2022 – 2023 - Dicado Sisalema, Leonel Adrián (2024)
The present case study with the topic "Overdue credit portfolio of the cooperative savings and credit Juan Pio de Mora Ltda., located in Caluma during the period 2022-2023", aims to evaluate its weight within the entity through of the horizontal analysis of your financial information. In addition, the aim is to determine the liquidity index of the cooperative and highlight the importance of proper management of this portfolio, as well as the need to recover overdue loans to avoid an increase in members' indebtedness. During the research, the theoretical foundations related to the credit portfolio, financial products, economic indicators and horizontal analysis were reviewed. This information was essential to obtain the results of the study. Both qualitative and quantitative approaches were adopted, and the inductive-deductive method was applied along with interviews as research tools, which allowed us to see that the financial institution faces an increase in its credit portfolio due to inadequate management, especially in the monitoring of overdue portfolio. The results of the study showed that the cooperative faces difficulties in managing credit recovery, despite having established requirements to ensure compliance with obligations by members.